Aplicación del Derecho Colectivo a la consulta previa, libre e informada en la sentencia del caso Pueblo Indígena Kiwcha de Sarayuku VS. Ecuador. - Moreno Duchicela, Kevin Vicente (2022)
This paper presents an analysis of the application of the collective right to prior, free and informed consultation within the Judgment of the Case of the Kiwcha Indigenous People of Sarayuku v. Ecuador. For that, a study is carried out on the prior, free and informed consultation from the doctrinal approach as a collective right of the indigenous peoples and according to the jurisprudence, through the Judgment of the Case of the Kiwcha Indigenous People of Sarayuku v. Ecuador, to determine the Ecuadorian State's observance of the right to consultation in accordance with the international standards applicable to this matter. The Ecuadorian State is responsible for the violation of the right to prior, free and informed consultation for the prospecting of non-renewable natural resources in the territory of the Sarayaku people, and also does not observe the general standards of consultation (free prior and informed) as well as the additional standards (good faith; adequacy and accessibility; and environmental impact study) set by the Inter-American Court of Human Rights.